Congenital Parasitaemia Among Neonates, the Malaria Risk Factors and Haematological Parameters Among Pregnant Women Attending Antenatal Clinic at Federal Medical Centre Makurdi, Benue State, Nigeria - M, Swem M.; U, Amuta E.; S, Houmsou R.; K, Okon; A, Swem C.I.; Y, Akwa V. (Darul Yasin Al Sys, 2024)
Malaria is a major public health problem, particularly among the vulnerable population of children aged less than 5years and pregnant women. Clinical impact of malaria disease is associated with high rate of morbidity and mortality. Consequential effect of malaria disease is the congenital transmission to neonates that result in diverse clinical syndrome, ranging from neonatal sepsis to jaundice. For better understanding of malaria epidemiology in pregnant women, the study eval__uate the preval__ence of malaria parasitaemia, associated risk factors and congenital transmission, using polymerase chain reaction technique to determine the Plasmodium speciation and genetic diversity. Study population was pregnant women at different gestational stage attending antenatal clinic of Federal Medical Centre, Makurdi Benue State. Systemic random sampling was employed in recruiting the study subjects, and a well-standardized questionnaire was administered before sample (blood) collection. The samples were analyzed using Rapid Diagnostic Test (RDT), Microscopic Smear Examination and Polymerase Chain Reaction (PCR). Overall malaria parasite detection was 3.6 % by PCR, 2.0% by RDT and 4.3% by Microscopy. Comparing the demographic variables with malaria parasitaemia, high level was recorded among pregnant women within age-group <20years(16.7%, 1/5) Location had high positivity among pregnant women in rural areas (10.5%,2/17,occupation(students, 6.0%,3/50), educational background(secondary, 6.2%, 8/121), marital status(non-married, 9.1%,2/20), parity(Secundigravidae)(4.8% 6/120), Malaria preventive measures, use of mosquito coil(8.0%,2/23), intermittent preventive therapy(Yes, 5.9%,8/127) and haematinic intake(Yes, 4.3%,4/89), Drainage provided(4.3% 4/90), source of water(well, 6.7%,6/83) High malaria parasitaemia reported in second trimester (7.3%, 7/96). eval__uating the effect of malaria parasitaemia on haematological indices, high malaria parasitaemia was recorded among pregnant women with haemoglobin (<11g/dl)(4.5%, 7/150). Significant difference was observed in malaria parasitaemia and PCV(0.37-0.47, 18.2%, 2/9).3.8%(11/282) in white blood cell count within 5-11X109, pregnant women with normal neutrophil count(40-60)(5.7%, 4/66), 5.9%(2/32) in pregnant women with increased lymphocyte, 4.1%(7/102)in monocytopenia cases, 9.1%(2/20) in eosinophilia(>4), 12.5%(1/7) in basophilia and 5.0%(2/38) in thrombocytopenia(<150000). The diagnostic technique, RDT vs PCR shows a significant difference (Kappa=0.898). Using the MSP-1 and MSP-2 primer of amplified Plasmodium falciparum species, msp-1 amplified two clones,K1 and MAD20, MSP-2 amplified two clones, FC27 and 3D7.All families amplified at different frequencies and varied base pairs, indicative of genetic diversity. In conclusion, the preval__ence of malaria parasitaemia among pregnant women was low, the genetic diversity of the various clones identified is consistent with studies conducted in Nigeria and sub-Saharan Africa, indicative of antimalarial therapy selective pressure. There was no congenital parasitaemia among the neonates.